Latihan Daya Tahan Otot Lengan 10 dan 8 Repetisi pada Siswa SLTP - I Gusti Agung Oka Negara (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
The purpose of this study is to examine the effects of muscular endurance traning on the arms of male students. Employing a pre and post test control group design, this study involved 16 junior high school students, assigned to pull the pulley as many times as possible. It was found that two models of muscular endurance training implemented in this study did not differ significantly although one model improved the muscular endurance more than the other.